Experimental Investigation of Hydraulic Fracturing and Stress Sensitivity of Fracture Permeability Under Changing Polyaxial Stress Conditions. Issue 12 (28th December 2020) - Fraser‐Harris, A. P.; McDermott, C. I.; Couples, G. D.; Edlmann, K.; Lightbody, A.; Cartwright‐Taylor, A.; Kendrick, J. E.; Brondolo, F.; Fazio, M.; Sauter, M.
Abstract: Understanding and predicting fracture propagation and subsequent fluid flow characteristics is critical to geoenergy technologies that engineer and/or utilize favorable geological conditions to store or extract fluids from the subsurface. Fracture permeability decreases nonlinearly with increasing normal stress, but the relationship between shear displacement and fracture permeability is less well understood. We utilize the new G eo‐ R eservoir E xperimental A nalogue T echnology (GREAT cell), which can apply polyaxial stress states and realistic reservoir temperatures and pressures to cylindrical samples and has the unique capability to alter both the magnitude and orientation of the radial stress field by increments of 11.25° during an experiment. We load synthetic analogue materials and real rock samples to stress conditions representative of 500–1, 000 m depth, investigate the hydraulic stimulation process, and then conduct flow experiments while changing the fluid pressure and the orientation of the intermediate and minimum principal stresses. High‐resolution circumferential strain measurements combined with fluid pressure data indicate fracture propagation can be both stable (no fluid pressure drop) and unstable (fluid pressure drop). The induced fractures exhibit both opening and shear displacements during their creation and/or during fluid flow with changing radial stress states. Flow tests during radial stress field rotation reveal that fracture normal effective stress has first‐order control on fracture permeability but increasing fracture offset can lead to elevated permeabilities at maximum shear stress. The results have implications for our conceptual understanding of fracture propagation as well as fluid flow and deformation around fractures. Key Points: Hydraulic stimulation, monitored with fiber optic strain sensors, shows both stable and unstable fracture propagation Controlled polyaxial stress with rotatable radial stresses are used to interrogate normal and shear stress controls on fracture fluid flow Fracture normal effective stress exerts first‐order control on fracture permeability but increasing offset can lead to elevated permeability